1999
DOI: 10.1002/(sici)1097-4547(19990815)57:4<417::aid-jnr1>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes: Glutamate producers for neurons

Abstract: In order for the brain to use the common amino acid glutamate as a neurotransmitter, it has been necessary to introduce a series of innovations that greatly restrict the availability of glutamate, so that it cannot degrade the signal-to-noise ratio of glutamatergic neurons. The most far-reaching innovations have been: i) to exclude the brain from access to glutamate in the systemic circulation by the blood-brain barrier, thereby making the brain autonomous in the production and disposal of glutamate; ii) to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
208
0
9

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 403 publications
(218 citation statements)
references
References 118 publications
1
208
0
9
Order By: Relevance
“…The observation that two such enzymes, GS and PC, are expressed only in astrocytes and not in neurons (24, 25, 77) was instrumental for our current view of the role of astrocytes in glucose and glutamate metabolism. Moreover, the use of primary cultures of astrocytes has been important for placing astrocytes as the cell in the brain providing the precursor glutamine for de novo biosynthesis of the main neurotransmitters, glutamate and GABA (78, 79). Interestingly, the transcriptomic analysis by Lovatt et al (66) provided evidence that the above mentioned enzymes are indeed exclusively found in astrocytes and not in neurons.…”
Section: Discoveries Made By Employing Primary Cultured Astrocytes Tomentioning
confidence: 99%
“…The observation that two such enzymes, GS and PC, are expressed only in astrocytes and not in neurons (24, 25, 77) was instrumental for our current view of the role of astrocytes in glucose and glutamate metabolism. Moreover, the use of primary cultures of astrocytes has been important for placing astrocytes as the cell in the brain providing the precursor glutamine for de novo biosynthesis of the main neurotransmitters, glutamate and GABA (78, 79). Interestingly, the transcriptomic analysis by Lovatt et al (66) provided evidence that the above mentioned enzymes are indeed exclusively found in astrocytes and not in neurons.…”
Section: Discoveries Made By Employing Primary Cultured Astrocytes Tomentioning
confidence: 99%
“…Therefore, it is suggested that they clear free synaptic GLU in a way resembling a buffer (Tong and Jahr 1994) instead of just a transporter. In the retina, glutamate not reabsorbed by the presynaptic EAATs is thought to be removed and recycled through a secondary process, which involves transporting into the Muller cell via its membrane EAAT1 and conversion into glutamine before transporting back to the photoreceptors (Hertz, Dringen et al 1999). …”
Section: Introductionmentioning
confidence: 99%
“…Astrocytes, in particular, are fundamentally important for rapid regulation of extracellular ions (Kofuji and Newman 2004; Olsen and Sontheimer 2008) and neurotransmitters (Conti et al 2004; Danbolt 2001), that, to a large extent, shape neuronal excitability and synaptic transmission. Astrocytes are critical for providing glutamatergic and GABA-ergic neurones with glutamine, which is indispensable for maintaining releasable pool of these transmitters (Hertz et al 1999); similarly, astrocytes are mainly responsible for adenosine turnover (Boison et al 2010). Astrocytes, unlike neurones, can synthesise glutamate de novo owing to the entry of pyruvate to the citric acid cycle via astrocyte-specific mitochondrial enzyme pyruvate carboxylase (Hertz and Zielke 2004).…”
Section: Astrocytes: the Homeostatic Cells Of The Cnsmentioning
confidence: 99%